2004
DOI: 10.1089/1549541041438632
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Affects Chemiluminescence of Carp(Cyprinus carpio)Blood Leukocytes

Abstract: These data show the inhibitory effect of visible light irradiation on blood leukocyte CL response in fish. These results suggest the prevention of host hyper-response which may occur under natural conditions of fish life. An Electron Paramagnetic Resonance (EPR) study of illuminated carp blood cells reveals the formation of Ascorbate free radicals (AFR) that may explain the decrease in reactive oxygen species (ROS) concentration following irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The study concluded that there were no negative side effects after the application of large doses of visible or infrared radiation and considerable systemic responses were exclusively found with ultraviolet irradiation [10]. Belotsky et al [11] studied the effect of visible-light irradiation of 5 J/cm 2 and 12 J/cm 2 applied to buffy coat leukocytes [11]. The study found an inhibitory effect dependent on the light intensity that was more pronounced at 12 J/cm 2 .…”
Section: Laser Chemistrymentioning
confidence: 99%
“…The study concluded that there were no negative side effects after the application of large doses of visible or infrared radiation and considerable systemic responses were exclusively found with ultraviolet irradiation [10]. Belotsky et al [11] studied the effect of visible-light irradiation of 5 J/cm 2 and 12 J/cm 2 applied to buffy coat leukocytes [11]. The study found an inhibitory effect dependent on the light intensity that was more pronounced at 12 J/cm 2 .…”
Section: Laser Chemistrymentioning
confidence: 99%
“…), but some references exist for other mammals (Nagahata et al, 1991;Lojek et al, 1997;Vuotto et al, 2000b;Letellier et al, 2001;McLaren et al, 2003;Khan, 2004;Pavelkova and Kubala, 2004). Limited information is available for other orders of vertebrates, such as fish (Kubala et al, 1996;Belotsky et al, 2004;Nikoskelainen et al, 2004Nikoskelainen et al, , 2006Verho et al, 2005), whereas almost nothing is available about amphibians (Marnila et al, 1995;Gilbertson et al, 2003) and birds (Laudert et al, 1993). Our initial studies for adapting this assay to wild birds were done in chickens because genetic differences are minimal among these inbred birds, and blood samples can be easily collected.…”
Section: Introductionmentioning
confidence: 99%